(untitled) (مجلة ديالى للبحوث الانسانية, 2025)
This study aims at investigating the effect of incorporating flipped classroom teaching strategy to enhance English language skills as Perceived by Iraqi EFL faculties` in Diyala University. To achieve the aim of the present study, the following hypothesis has been put: There is no statistically significant differences at (á≤0.05) between the attitude of EFL faculties towards the effect of incorporating flipped classroom teaching strategy to enhance English language skills due to gender, qualification, years of experience and specialization. The sample of the study was purposive consisted of 45 instructors (23 males and 22 females) from English department College of basic education, and college of education for human sciences University of Diyala, during the academic year (2024 -2025). Meanwhile a mixed method approach employing both qualitative and quantitative method was adopted. Data were collected through a questionnaire. The results showed that the total degree of the effect of incorporating in enhancing the four skills of English language as Perceived by Iraqi EFL faculties` in Diyala University scored a higher level of estimation. Furthermore, in relation to the hypothesis, the results showed that there were no statistically significant differences in the attitudes of English language faculties towards the effect of incorporating the flipped classroom in enhancing the four skills due to gender, qualification, and specialization. However, statistically significant differences were found due to years of experience variable. The study recommended to integrate specific content and activities into the EFL curricula through utilizing technological advancements including YouTube videos, website links social media, and the like, and also recommended to integrate flipped classrooms strategy in teaching English language skills as it has been found highly beneficial in both physical learning and virtual learning.